STIM1L is a new actin-binding splice variant involved in fast repetitive Ca(2+) release - Darbellay, Basile (The Rockefeller University Press, 2011)
Cytosolic Ca(2+) signals encoded by repetitive Ca(2+) releases rely on two processes to refill Ca(2+) stores: Ca(2+) reuptake from the cytosol and activation of a Ca(2+) influx via store-operated Ca(2+) entry (SOCE). However, SOCE activation is a slow process. It is delayed by >30 s after store depletion because stromal interaction molecule 1 (STIM1), the Ca(2+) sensor of the intracellular stores, must form clusters and migrate to the membrane before being able to open Orai1, the plasma membrane Ca(2+) channel. In this paper, we identify a new protein, STIM1L, that colocalizes with Orai1 Ca(2+) channels and interacts with actin to form permanent clusters. This property allowed the immediate activation of SOCE, a characteristic required for generating repetitive Ca(2+) signals with frequencies within seconds such as those frequently observed in excitable cells. STIM1L was expressed in several mammalian tissues, suggesting that many cell types rely on this Ca(2+) sensor for their Ca(2+) homeostasis and intracellular signaling.